Garuda Indonesia’s Business Strategy Formulation Air Cargo Corporation in 2023 - Charles. An; Afizal Candra; Hendy Sepriandi; Muhammad Dhyra Pratama (Green Publisher, 2025)
PT Garuda Indonesia is an airline that not only provides passenger transportation services but also offers cargo delivery services through a specialized organization known as SBU Garuda Cargo. A Strategic Business Unit (SBU) is an independent business unit under the company's umbrella aimed at optimizing resources and maximizing the company's value. The company experienced a 71.36% decrease in the volume of air cargo transportation from 2018 to 2022. The objective of this research is to examine the formulation of strategies for PT Garuda Indonesia. The research type used is qualitative descriptive research, utilizing SWOT analysis to process the data. Therefore, it is crucial for PT Garuda Indonesia to promptly implement appropriate mitigation efforts to increase the volume, establish competitive advantages, and ensure sustainability in its Air Cargo Business.